2021
DOI: 10.56348/jos3.v1i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Study on The Relationship Between Social Support and Entrepreneurship Intention Experienced by Adolescents

Abstract: Entrepreneurship is very important for the community because with entrepreneurship people are no longer dependent on jobs, and create job opportunities for others. Entrepreneurial activities in the community have a very important role to help overcome the problem of unemployment and increase people's income. The cause of the large number of unemployed because most people do not have an entrepreneurial spirit. The social environment has an important role in shaping the desire for entrepreneurship. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
2
3
0
1
Order By: Relevance
“…If there is suitable support available to the individual, it has a positive influence on the individual because such support can shape one's attitude, self-efficacy, and behavioral control. The literature also supports the influence of relational support on entrepreneurship (Khayru et al, 2021;Moussa and Kerkeni, 2021). The results are consistent with the literature and highlight the role of perceived relational support (Osorio et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…If there is suitable support available to the individual, it has a positive influence on the individual because such support can shape one's attitude, self-efficacy, and behavioral control. The literature also supports the influence of relational support on entrepreneurship (Khayru et al, 2021;Moussa and Kerkeni, 2021). The results are consistent with the literature and highlight the role of perceived relational support (Osorio et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, a low level of support is associated with less intention to involve in entrepreneurial activity (Moussa and Kerkeni, 2021). Previous studies indicate that relational support such as from family and friends is an important factor in promoting entrepreneurship among individuals (Abebe et al, 2014;Fizza (2017); Khayru et al, 2021). The relationship between relational support and the TPB is such that such support can shape an individual entrepreneurshiprelated attitude, make an individual feel entrepreneurship is a norm, and enable a higher perceived behavioral control.…”
Section: Perceived Support Model and The Dimensions Of The Theory Of ...mentioning
confidence: 99%
“…SS influences ESE directly and significantly (H2). The findings support the hypothesis proposed in earlier studies ( Khayru et al, 2021 ; Bui Ngoc Tuan and Pham, 2022 ). Bui Ngoc Tuan and Pham (2022) found that ESE is proportional to the amount of SS an individual receives from the surrounding environment.…”
Section: Discussionsupporting
confidence: 93%
“…The hope of being accepted into the world of work is certainly not a mistake, but it cannot be denied that job opportunities are very limited and not directly proportional to graduates of higher education institutions (Usman & https://equatorscience.com/index.php/jabter Simare Mare, 2020). In addition, the government is expected to make efforts through educational policies to change the paradigm so that students are more prepared for entrepreneurship and graduates do not only focus on becoming employees (Khayru et al, 2021;Steyn, 2020). Entrepreneurship is a choice to overcome the increasing unemployment problem.…”
Section: Introductionmentioning
confidence: 99%